Differences between the Leaf Mycobiome of Coffea arabica and Wild Coffee Species and Their Modulation by Caffeine/Chlorogenic Acid Content - Leandro Pio de Sousa (MDPI AG, 2021)
The study of microbes associated with the coffee tree has been gaining strength in recent years. In this work, we compared the leaf mycobiome of the traditional crop Coffea arabica with wild species Coffea racemosa and Coffea stenophylla using ITS sequencing for qualitative information and real-time PCR for quantitative information, seeking to relate the mycobiomes with the content of caffeine and chlorogenic acid in leaves. Dothideomycetes, Wallemiomycetes, and Tremellomycetes are the dominant classes of fungi. The core leaf mycobiome among the three Coffea species is formed by Hannaella, Cladosporium, Cryptococcus, Erythrobasidium, and Alternaria. A network analysis showed that Phoma, an important C. arabica pathogen, is negatively related to six fungal species present in C. racemosa and C. stenophylla and absent in C. arabica. Finally, C. arabica have more than 35 times the concentration of caffeine and 2.5 times the concentration of chlorogenic acid than C. stenophylla and C. racemosa. The relationship between caffeine/chlorogenic acid content, the leaf mycobiome, and genotype pathogen resistance is discussed.